DAKWAH TERAPETIK: SOLUSI ATAS PROBLEM MANUSIA MODERN - Muskinul Fuad (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
In this modem era, human beings are facing various crisis or multidimensional problems. Material welfare following the development of Science and technology does not easily give them real happiness. They have been the victims of globalization. In such condition, the role of daâ€™i as a â€œdoctorâ€ of the sick souls is really needed to recover the victims of globalization. Therapeutic da â€™wa is an altemative solution of this serious problem. Da â€™wa with this approach is developed on the basis of religionâ€™s function as a therapy. This function requires deep study of therapeutic aspects in Islamic teachings. This effort can be seen from esoteric dimension of Islam.